Análise de erros em matemática na perspectiva do professor que ensina matemática nos anos finais do ensino fundamental - Penha, Rodolfo Sena da (2023)
It is known that learning difficulties in the subject of mathematics have permeated the school life of students at different levels of Basic Education, as well as being the subject of discussion in study groups by teachers and researchers in the field. From this perspective, it is understood that understanding students' mistakes not only benefits students individually, but also allows teachers to rethink more effective and meaningful teaching practices, contributing to a richer and more adaptable educational environment for learning. The aim is to analyze the different types of errors made by students in mathematics, using them as a didactic-pedagogical tool in the teaching and learning processes of this subject. It is based on the thesis that understanding students' errors allows the teacher to diagnose conceptual understanding, personalize teaching, provide more specific support to address students' learning difficulties, in addition to the possibility of adjustments to teachers' teaching strategies. To carry it out, a qualitative, exploratory methodology was adopted, as well as the content analysis technique to examine and interpret the data. The research was carried out with a group of teachers from the municipal network of Guaramiranga – CE, based on an extension course. The extension course was training aimed at teachers who teach mathematics in the final years of Elementary School in the municipality of Guaramiranga and for mathematics teachers in general, taught by members of the Grupo Tecendo Redes Cognitivas de Aprendizagem (G-TERCOA/CNPq). Data were collected through targeted activities and semi-structured interviews. We sought to direct the activities developed in this investigation with the aim of collecting data on evidence of learning and error analysis, based on participant observation. The results indicate, based on the teachers' speeches and experiences, the experience in the extension course and the collaboration of the discussions of the GTERCOA/CNPq members that the identification and understanding of errors is part of the learning process. Important reflections were highlighted, such as the understanding that errors help improve student performance, promote an adaptive environment, encourage students to explore challenging concepts and actively participate in classes, understanding errors as learning opportunities.